Nutrition, pH, Temperature, and Humidity Monitoring Hydroponics System based on Android - Prihatin Oktivasari; Muda Wali Samudra Pasai; Mustofa Mustofa; Royhan Royhan; Asep Kurniawan (National Research and Innovation Agency, 2024)
Agriculture plays a very important role in the lives of Indonesian people. With technological advances and the increasing limitation of agricultural land, the patterns of matching crops in societies have changed. Innovations have been implemented, one of which is the use of technology such as hydroponic systems. One of the main factors that influence the success of hydroponic methods is temperature and humidity. The research aims to design and develop an autonomic control system that uses Fuzzy Logic to regulate the temperature and moisture of hydroponic plants, as well as to design the control of the nutrition and pH supply of hydrogen plants. Hydroponics plant control systems are implemented using microcontrollers and DHT22, TDS sensors, and pH sensors. In addition, an Android-based interface has been developed to monitor and control the system remotely via an internet connection. In this study the accuracy of the TDS sensor is 96.5%, the pH sensor was 98.19%, and the precision of the Fuzzy logic system at temperature and humidity is 100%